Quantitative cardiac autonomic outcomes of hydrotherapy in women during the first stage of labor - Dias, Raquel Aparecida; de Faria Cardoso, Cláudia; Ghimouz, Rym; Nono, Daniel Alessander; Silva, José Antônio; Acuna, Juan; Baltatu, Ovidiu Constantin; Campos, Luciana Aparecida (Frontiers in Medicine, 2023)
Introduction: Most hydrotherapy studies during childbirth report findings related to pain using a widespread set of subjective measures. In this study, ECG biomarkers as quantitative cardiac autonomic outcomes were used to assess the effects of warm shower hydrotherapy on laboring women during the first stage of labor. Methods: This was a prospective single-blind cohort study on stage I delivering women. Their cardiac autonomic function was assessed using heart rate variability (HRV) measures during a deep breathing test using point-of-care testing comprised of an HRV scanner system with wireless ECG enabling real-time data analysis and visualization. Labor pain and anxiety were assessed using the Visual Analogue Scale for Pain (VASP) and the Beck Anxiety Inventory (BAI). A total of 105 pregnant women in the first stage of labor who received warm shower hydrotherapy, intravenous analgesia (scopolamine + sodium dipyrone), or spinal anesthetic (bupivacaine + morphine) were enrolled. Results: In women during the first stage of labor, parasympathetic modulation reflected through RMSSD (root mean square of successive RR interval differences) was significantly reduced by hydrotherapy and intravenous analgesia (before vs. after mean rank diff. 35.73 and 65.93, respectively, p <0.05). Overall HRV (SDNN, standard deviation of RR intervals) was significantly decreased only by intravenous analgesia (before vs. after mean rank diff. 65.43, p <0.001). Mean heart rate was significantly increased by intravenous analgesia, while spinal anesthesia reduced it, and hydrotherapy did not alter it (before vs. after mean rank diff. -49.35*, 70.38*, -24.20NS, respectively, * p <0.05, NS not significant). Conclusions: This study demonstrates that warm shower therapy may impact the sympathovagal balance via parasympathetic withdrawal in women during the initial stage of labor. The findings of this study provide quantitative support for using warm shower hydrotherapy during labor via point-of-care testing. The dependability of hydrotherapy as a nonpharmacological treatment is linked to the completion of more clinical research demonstrating quantitative evidence via outcome biomarkers to support indications on stress and birth progress.